Integrated Continuous Healthcare Team Computer System Architecture - Caeiro, J. (2020)
A computer-based pattern recognition system architecture destined to collect and process geographically referenced data about integrated continuous healthcare teams (ECCI) is presented and discussed in the chapter. These teams are part of Portugal's National Network of Integrated Continuous Care (RNCCI). The system is designed to collect data about the displacement of each team during healthcare assistance. The pattern recognition system handles information about the costs related to the provided healthcare. The architecture is designed around open source software resources. Virtual machines and container-based technologies provide hardware independence. The Python programming language ecosystem is chosen for all the main components of the sy